Optimal and Heuristics Policies for a Multiechelon Inventory Problem with Secondary Market Sales - ANGELUS, Alexandar (Institutional Knowledge at Singapore Management University, 2010)
Most research on supply chain management deals with settings where firms do not voluntarily get rid of inventory in the system. Since voluntary inventory reductions are often observed in practice, in this paper, we propose a (multi-echelon) model where the firm can dispose of excess stock through sales in the secondary market at each stage in the supply chain. What are called nested echelon base stock policies are shown to be optimal. Secondary market sales complicate the structure of the system, so that the classical Clark and Scarf (1960) approach no longer applies. Nevertheless, we identify features of the optimal policy that significantly reduce the state space and simplify the computation, by providing conditions under which it is optimal for the firm not to both dispose of stock and order additional inventory. Finally, we formulate a class of disposal policies that achieves the Clark-Scarf decomposition, and reduces the optimal inventory policy to the classical echelon base stock policy. A numerical study demonstrates the performance of these policies as heuristics, illustrates the value of secondary markets to the supply chain, and provides managerial insights.